A Pedagogical Evaluation of Intra-Sentential Code-Switching Patterns in L2 Classroom Talk - Majer, Jan (Research in Language, 2009)
The paper is concerned with teachers’ and students’ alternation between L1 and L2 within the same utterance, i.e. uses of intra-sentential code-switching which in classroom discourse tends to be less accepted by modern language pedagogy than its inter-sentential counterpart. The rationale for the study is the universal nature of the phenomenon known to occur in the first place in interactions among natural bilinguals and multilinguals. The data analysis sections of the article review eight different patterns which are evaluated pedagogically. It transpires that the category most likely to arouse methodological controversy is code-mixing.